Integration of Metabolomics and Proteomics in Exploring the Endothelial Dysfunction Mechanism Induced by Serum Exosomes From Diabetic Retinopathy and Diabetic Nephropathy Patients - Yang, Jing; Liu, Dongwei; Liu, Zhangsuo (Frontiers in Endocrinology, 2022)
Background: The prevalence of diabetic microvascular diseases has increased significantly worldwide, the most common of which are diabetic nephropathy and retinopathy. Microvascular endothelial cells are thought to be major targets of hyperglycemic damage, while the underlying mechanism of diffuse endothelial dysfunction in multiple organs needs to be further investigated. Aim: The aim of this study is to explore the endothelial dysfunction mechanisms of serum exosomes (SExos) extracted from diabetic retinopathy and nephropathy (DRDN) patients. Methods: In this study, human glomerular endothelial cells (HGECs) were used as the cell model. Metabolomics (UPLC-MS/MS) and proteomics (TMT-based LC-MS/MS) together with bioinformatics, the correlation analysis and the joint pathway analysis were employed to discover the underlying mechanisms of endothelial dysfunction caused by patient’s SExos from. Results: It can be assumed that patients’ SExos might cause endothelial dysfunction mainly by upregulating FIBA and downregulating 1-Methylhistidine (1-MH). Bioinformatics analysis pointed to an important role in reducing excess cysteine and methionine metabolism. Conclusion: FIBA overexpression and 1-MH loss may be linked to the pathogenicity of diabetic endothelial dysfunction in DR/DN, implying that a cohort study is needed to further investigate the role of FIBA and 1-MH in the development of diabetic nephropathy and retinopathy, as well as the related pathways between the two proteins.